Length-weight relationship of five species of rays from Mumbai, Maharashtra - Raje, Sadashiv Gopal (Indian Journal of Fisheries, 2011)
The length-weight relationship of five species of rays revealed no significantdifference between males and females. Hence, regression equation for each specieswas calculated as : Dasyatis uarnak: Log W = -7.73348 + 2.54483 Log L., D. sephen:Log W = -8.09534 + 2.62806 Log L, Trygon walga: Log W = -7.47977 + 2.48397Log L., Gymnura micrura: Log W = -9.91272 + 2.73408 Log L and Rhinopterajavanica: Log W = -9.24263 + 2.67815 Log L.